Topoloģiskā saistība un haoss - Alkšare, Agnese (Latvijas Universitāte, 2006)
Darbā dots pārskats par divu veidu saistībām starp funkcijām: saistību (vai pussaistību) un topoloģisko saistību. Jēdzieni ilustrēti ar piemēriem.

This work is giving overview of two means of conjugacy between functions: conjugacy (or semiconjugacy) and topological conjugacy. Terms are illustrated with examples.
Topological conjugacy and chaos
Keywords: Matemātika